LPA Brief no. 13. The spatial integration of livestock markets in Niger - Fafchamps, M.; Gavian, S. (International Livestock Research Institute, 1998)
Livestock make an important contribution to the livelihood of Sahelian farmers and herders, and are a source of insurance against income shocks brought about by weather and economic disruptions. By allocating livestock more efficiently over space, spatial market integration should favour a sustainable use of scarce pasture resources. The geographical integration of markets is also critical for the prevention of entitlement failures and the insurance value of livestock. To be effective, strategies providing protection against local weather shocks require livestock prices to be relatively stable so that risk is shared over space and idiosyncratic price variations are smoothed. Studying the spatial integration of livestock markets in the Sahel is thus important for optimal and sustainable natural resource use, early warning, market and trade policies. This study sheds some light on the integration of livestock markets in a representative Sahelian country, Niger.